Guarding the boundaries: a Swedish policy debate about geography and education for sustainable development - Hampus Hallingfors; Henrik Åström Elmersjö (Nordic Journal of Studies in Educational Policy)
In this article, we analyse how educational policy debates regarding specific school subjects are related to the demarcation of science. Utilising boundary-work theory we analyse material from a later abandoned revision process for the Swedish upper secondary school curriculum in 2004–2006. During this process a new subject – Sustainable Development – was proposed by the Swedish National Agency for Education. As a consequence, the Geography subject, potentially a suitable arena to naturally handle education for sustainable development, would be given a very peripheral role in the upper secondary school curriculum. From the suggestion a debate about scientific boundaries arose, with arguments that may be traced back to the theoretical concepts; ‘exclusion’, ‘expansion’ and ‘protection of autonomy’.